Using GIS to locate waste bins a case study on Kolkata City, India - Paul, Koushik (Journal of Environmental Science and Management, 2017)
Environmentally acceptable management of Municipal Solid Waste (MSW) has become a challenge due to limited resources, increasing population and rapid urbanization. Kolkata city, with an area of 187.33 km2 and a population of about 10 million (including a oating population of about 6 million), generates about 3,500 MT of solid waste per day. Daily disposal rate of solid waste at Dhapa exceeds 3,000 MT d-1 while at Garden Reach the disposal is 100-150 MT d-1. Conservancy staff collects waste from households and streets and dumps them at skips/MS containers (55%) or at open vats (45%). Collected waste is transported directly to disposal ground at Dhapa by KMC departmental vehicles and KMC-hired vehicles. Lack of proper planning and inadequate data regarding solid waste generation and collection compound the solid waste management problem. GIS as a tool can recognise, correlate and analyse relationship between spatial and non-spatial data- it can thus be used as a decision support tool for efficient management of the different functional elements solid waste e.g. bin location, number of bins required, waste transportation, generating work schedules for workers and vehicles. This study examines GIS application in assisting locational analysis of waste bins in Kolkata and optimise the overall solid waste collection process.